Current trends in inflammatory and immunomodulatory mediators in sepsis - Aziz, Monowar (Society for Leukocyte Biology, 2013)
Sepsis refers to severe systemic inflammation in response to invading pathogens. An overwhelming immune response, as mediated by the release of various inflammatory mediators, can lead to shock, multiple organ damage, and even death. Cytokines, proteases, lipid mediators, gaseous substances, vasoactive peptides, and cell stress markers play key roles in sepsis pathophysiology. Various adhesion molecules and chemokines sequester and activate neutrophils into the target organs, further augmenting inflammation and tissue damage. Although the anti-inflammatory substances counterbalance proinflammatory mediators, prolonged immune modulation may cause host susceptibility to concurrent infections, thus reflecting enormous challenge toward developing effective clinical therapy against sepsis. To understand the complex interplay between pro- and anti-inflammatory phenomenon in sepsis, there is still an unmet need to study newly characterized mediators. In addition, revealing the current trends of novel mediators will upgrade our understanding on their signal transduction, cross-talk, and synergistic and immunomodulating roles during sepsis. This review highlights the latest discoveries of the mediators in sepsis linking to innate and adaptive immune systems, which may lead to resolution of many unexplored queries.